Heavy metal bioaccumulation in honey bee matrix, an indicator to assess the contamination level in terrestrial environments. (January 2020) - Goretti, E.; Pallottini, M.; Rossi, R.; La Porta, G.; Gardi, T.; Cenci Goga, B.T.; Elia, A.C.; Galletti, M.; Moroni, B.; Petroselli, C.; Selvaggi, R.; Cappelletti, D.
Abstract: The most significant risk factor for organisms living in an environment contaminated by heavy metals is the metal bioavailability. Therefore, an efficient ecotoxicological approach to metal contamination is the measure of bioaccumulation level in target organisms. In this work, we characterized the heavy metal bioaccumulation in honey bees, Apis mellifera ligustica, collected at 35 sites from Umbria (Central Italy). The comparison of our data with selected Italian investigations revealed metal bioaccumulation in honey bee matrix of the same order of magnitude, with Cd showing a higher variability. To generalize the results, we developed a Honeybee Contamination Index (HCI) based on metal bioaccumulation in honey bees. An application of the HCI to the present dataset revealed cases of low (sixteen sites), intermediate (eighteen sites), and high (one site) metal contaminations. The comparison of HCI values from the Umbrian dataset with values calculated for other Italian and European metadata showed that most of the Umbrian sites fell in the portion of low and intermediate contamination conditions. HCI represented a reliable tool that provided a piece of concise information on metal contamination in terrestrial environments. Parallel to this effort, we have determined, the metal concentrations in the airborne particulate matter (PM10 ) at three regional background-monitoring stations in Umbria. These stations are representative of the average air quality of the areas of the investigated apiaries. A comparative analysis of metal enrichment factors in PM10, and honey bees suggested that the contamination in the bees was related to the PM10 values only to a minor extent. On the other side, a clear enrichment of metals such as Cd, Mn, Zn, and Cu in the honey bees appeared to depend on very local conditions and was probably related to the use of pesticides and fertilizers, and the resuspension of the locally contaminated soils and agriculture residues. Graphical abstract: Image 1 Highlights: Honey bee Contamination Index has been developed to evaluate metal contamination. HCI formulated a judgment of regional metal contamination in terrestrial environments. HCI values of the Umbrian sites fell between low and intermediate contamination level. HCI compared the heavy metal contamination among Italian and European regions. Metal bioaccumulation in honey bees was related to the PM10 only to a minor extent.